2014
DOI: 10.3389/fpls.2014.00317
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate reductase 15N discrimination in Arabidopsis thaliana, Zea mays, Aspergillus niger, Pichea angusta, and Escherichia coli

Abstract: Stable 15N isotopes have been used to examine movement of nitrogen (N) through various pools of the global N cycle. A central reaction in the cycle involves the reduction of nitrate (NO−3) to nitrite (NO−2) catalyzed by nitrate reductase (NR). Discrimination against 15N by NR is a major determinant of isotopic differences among N pools. Here, we measured in vitro 15N discrimination by several NRs purified from plants, fungi, and a bacterium to determine the intrinsic 15N discrimination by the enzyme and to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…), or even higher (Carlisle et al . ). If E / I is recalculated using 22‰ for both enzymes, E / I using the isotope mass balance decreases and the similarity between the two methods increases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…), or even higher (Carlisle et al . ). If E / I is recalculated using 22‰ for both enzymes, E / I using the isotope mass balance decreases and the similarity between the two methods increases.…”
Section: Discussionmentioning
confidence: 97%
“…4 and 5 assume discrimination factors of 15.4‰ for nitrate reductase (Ledgard et al 1985) and 16.8‰ for glutamine synthetase (Yoneyama et al 1993). However, more recent work has suggested that the discrimination factor of nitrate reductase is closer to 22-26‰ (Needoba et al 2004;Tcherkez and Farquhar, 2006;Karsh et al 2012), or even higher (Carlisle et al 2014). If E/I is recalculated using 22‰ for both enzymes, E/I using the isotope mass balance decreases and the similarity between the two methods increases.…”
Section: Compartmental Analysis Of Tracer Efflux and Isotope Mass Balmentioning
confidence: 99%
“…Voss et al ). A recent study, however, reported a more elevated 15 ε for Nar purified from Escherichia coli of 31.6‰ using benzyl viologen as a reductant (Carlisle et al ). This estimate, however, derived from a 2‐point regression on the δ 15 N of the NO2 product and is thus subject to considerable uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…We concur with this recommendation and suggest that any concentration ≥2 at% 15 N is sufficient to introduce alterations in algal metabolism. Moreover, Carliste et al 31. have demonstrated that experiments with enriched 15 N tracers consistently produce lower estimates for N cycling rates than those conducted using natural abundance or non-isotopic methods.…”
Section: Discussionmentioning
confidence: 99%